REVIEW OF NANOMATERIALS FOR REMEDIATION OF PETROLEUM IMPACTED SOIL AND WATER (FUDMA JOURNAL OF SCIENCES, 2023)
This paper reviews nanoremediation technologies and potential nanomaterials for oil spill remediation in Nigeria. Oil spillage in the Niger-Delta area of Nigeria emanating from oil and gas operations is a topical issue currently and has resulted in serious environmental degradation leading to loss of human, material and economic resources. Oil polluted soil and water can be remediated with different techniques but the use of existing conventional remediation technologies has limited or partial effectiveness and this has given rise to the integration of these methods in oil spill clean-up. However, more innovative and eco-friendly technologies to enhance clean-up operations especially for major oil spills are also needed. Nanoremediation is one such technology and various nanomaterials can used for the clean-up of oil spill impacted soil and waterbodies due to the advantages it has over conventional technologies. Secondary sources of data (journal papers, textbooks, internet and library) were utilized for the study which analysed the extent of oil spill in the Nigerian environment, causes of oil spill and the current remediation technologies used for oil spill clean-up. The characteristics and potential applications of relevant nanoremediation technologies for oil spill impacted soil and water bodies are presented. These include: nanobioremediation, carbon-based nanomaterials; metal-based nanomaterials (nano-zerovalent iron (nZVI) and Fe3O4); nanocomposites (zeolites and magnetic carbon-metal nano-composites). The environmental implications and safeguards for the use of nanomaterials are also considered
Keywords: Oil spill, clean-up, Niger Delta, nanoremediation